2006
DOI: 10.1590/s1413-81232006000300015
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho do PSF no Sul e no Nordeste do Brasil: avaliação institucional e epidemiológica da Atenção Básica à Saúde

Abstract: A pesquisa, desenvolvida dentro dos Estudos de Linha de Base do Proesf analisou o desempenho do Programa Saúde da Família (PSF) em 41 municípios dos Estados de Alagoas, Paraíba, Pernambuco, Piauí, Rio Grande do Norte, Rio Grande do Sul e Santa Catarina. Utilizou delineamento transversal, com grupo de comparação externo (atenção básica tradicional). Entrevistou 41 presidentes de Conselhos Municipais de Saúde, 29 secretários municipais de Saúde e 32 coordenadores de Atenção Básica. Foram caracterizados a estrutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
1
154

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(228 citation statements)
references
References 22 publications
3
70
1
154
Order By: Relevance
“…As an example, the expansion of family health teams between 1999 and 2004 was greater in the Northeast region than in the South region. 9 Considering the fact that the outcome was assessed with the question about medical diagnosis, it is assumed that the increase in access to and use of health services could partly explain the increase in asthma prevalences, especially in the rural area.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the expansion of family health teams between 1999 and 2004 was greater in the Northeast region than in the South region. 9 Considering the fact that the outcome was assessed with the question about medical diagnosis, it is assumed that the increase in access to and use of health services could partly explain the increase in asthma prevalences, especially in the rural area.…”
Section: Discussionmentioning
confidence: 99%
“…Camargo Jr et al 4 analyzed three information systems and concluded that SIAB has adequate coverage and reliability and that these data should be used in order to value the information systems and to stimulate their use as monitoring and evaluation instruments. Fachini, 9 on the other hand, argues that the information provided by the SIS is fragmented, is not updated and its quality is low. According to Cordeiro et al, 7 data from SIAB are not valued by the team's nurse, a fact that may infl uence the quality of their collection, since these professionals are the supervisors of the Community Health Agents.…”
Section: Discussionmentioning
confidence: 99%
“…A população-alvo do estudo foi constituída por todos os trabalhadores lotados em 240 UBS da zona urbana de 41 municípios com mais de 100 mil habitantes de sete estados das regiões Sul (Rio Grande do Sul, Santa Catarina) e Nordeste (Alagoas, Paraíba, Pernambuco, Piauí, Rio Grande do Norte), incluídos no 16 .…”
Section: Metodologiaunclassified
“…Apesar da historicidade das relações entre precárias condições de trabalho e de saúde dos trabalhadores 1,14,15 , há relativa escassez de investigações epidemiológicas abordando essa temática na força de trabalho em saúde, particularmente na atenção primária à saúde 8,9,16,17 . No campo das morbidades, os transtornos mentais promovem importantes prejuízos na funcionalidade e qualidade de vida.…”
Section: Introductionunclassified